The paschen discontinuity in B stars - Ringuelet, Adela Emilia (1969)
Measurements of the Paschen discontinuity in stars withT eff ≥104K leads to the conclusion that the D P/DB ratio increases with temperature faster than expected. The increase of D P/DB with (logg)−1 is also steep.